Ethnicity and Homicide in California, 1850-1900 - McKanna, Clare V. Jr ([Verlag nicht ermittelbar], 1992)
This data collection explores the relationship between homicide and ethnicity in California during 1850-1900. The data are presented in three files. Part 1, Homicide, includes information on time, place, location, and cause of the crime for all murder cases in seven California counties. The relationship between the victim and the accused, and the race, sex, age, and occupation of each are also provided. Part 2, Indictment, includes information on criminal charge, plea, verdict, and sentence for all murder trials in the same seven counties during the time period. Part 3 provides information on all prisoners incarcerated in California for murder. Included are age, sex, ethnicity, place of birth, and occupation of each prisoner, as well as sentence, disposition of case, years served, and year in which the prisoner was released.